The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1111/1750-3841.13585
|View full text |Cite
|
Sign up to set email alerts
|

Food Safety Crisis Management—A Comparison between Germany and the Netherlands

Abstract: In order to prevent food safety incidents from becoming a crisis, a good crisis management structure is essential. The aim of the current study was to compare and evaluate the national food incident response plans of 2 neighboring EU Member States: Germany and the Netherlands. This revealed that the structure of these plans is comparable, starting with initial alerting, assessment of the problem, upscaling, an execution phase and finally an evaluation of the crisis management. However, the German communication… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 14 publications
(22 reference statements)
0
10
0
Order By: Relevance
“…The Federal Ministry of Food and Agriculture and the Federal Office of Consumer Protection and Food Safety (BVL) are responsible for RM at national level. The BVL coordinates regional activities ( BfR, 2011 g ; van Asselt et al., 2017 ). RM is performed at national level in a crisis situation, as defined in Regulation No 178/2002 (EC, 2002 ).…”
Section: Resultsmentioning
confidence: 99%
“…The Federal Ministry of Food and Agriculture and the Federal Office of Consumer Protection and Food Safety (BVL) are responsible for RM at national level. The BVL coordinates regional activities ( BfR, 2011 g ; van Asselt et al., 2017 ). RM is performed at national level in a crisis situation, as defined in Regulation No 178/2002 (EC, 2002 ).…”
Section: Resultsmentioning
confidence: 99%
“…Although the FDA has some authority to issue recalls, it generally is the action of last resort [15]. In order for risks not to turn into full-blown crises, it is important to start risk communicating as early as possible [5,16]. van Asselt et al [16] evaluated food safety response plans in Germany and Netherlands and found that the success of a food safety campaign depended on the way the public was alerted initially followed by assessment of the problem, quick planning and execution of solutions.…”
Section: Risk Communicationmentioning
confidence: 99%
“…With the improvement of the living standard, increasing attention is paid to food safety. In the past few years, food safety incidents have occurred persistently and aroused global concern. Safe and nutritive food consumption is the basic requirement and prerequisite for the physical and mental health of human bodies. Furthermore, one of the most important causes of food safety problems is the diversified food hazards and contaminants, and the increasing complexity of the food system also aggravates the challenge of food safety .…”
Section: Introductionmentioning
confidence: 99%